The Gap between Theory and Action through a Model for Classroom Inquiry - Rafiepour, Abolfazl (Universitas Ahmad Dahlan, 2017)
This paper reports an investigation about lower secondary teacher professional development program in Iran that seventy teachers of mathematics participate on that. In this program, lesson study and action research are used to create a model for classroom inquiry. The first and important purpose of this model was to filling the gap between theory and action. Results of this study show that it is possible to combine lesson study and action research. Finding of this study also show that using the model for classroom inquiry can be helpful in decreasing the gap between theory and action. Finally, paper will be finish by introducing some obstacle that occurred within the accomplishment of the teacher professional development program.